Analysis of genetic differentiation and phylogenetic relationship between Changium smyrnioides and Chuanminshen violaceum using molecular markers and ITS sequences - TAO Xiao-yu; GUI Xian-qun; FU Cheng-xin; QIU Ying-xiong (浙江大学学报. 农业与生命科学版, 2008)
The data from RAPD, ISSR analysis, and the sequences of the nrDNA internal transcribed spacer (ITS) were used to evaluate the genetic differentiation and phylogenetic relationship between Changium smyrnioides and Chuanminshen violaceum. Six wild populations of C. smyrnioides and one cultivated population of C. violaceum were studied by ISSR and RAPD analysis. The results show that the genetic variation of C. smyrnioides was high and the majority of genetic variation occurred among populations. Cluster analysis (UPGMA) indicated that substantially genetic divergence was found between C. smyrnioides and C. violaceum at DNA level. The sequences of ITS-1 in six populations of C. smyrnioides ranged from 215 bp to 219 bp in size and those of ITS-2 from 224 bp to 227 bp, The G+C contents of ITS-1 varied from 58.3% to 59.2%, and those of ITS-2 varied from 54.3% to 56.6%. ITS sequence analysis also revealed certain differences between C. smyrnioides and C. violaceum. ITS regions from C. smyrnioides, C. violaceum and relative species in Apioideae were sequenced and analyzed. Results strongly support the systematic position of C. smyrnioides. In the ITS phylogenetic trees, C. violaceum was sister to C. smyrnioides with high bootstrap values (100%), suggesting that C. violaceum should be placed in Smyrnieae Koch.